Blessing or curse? The impacts of non-agricultural part-time work of the large farmer households on agricultural labor productivity - Jiang, Xin; Zhong, Shihu; Huang, Cancan; Guo, Xiaoxin; Zhao, Jingjing (Technological and Economic Development of Economy, 2022)
This study analyzes the mechanism of coexistence of non-agricultural part-time work of farmer households and large-scale cultivation of cultivated land, and the effect of non-agricultural part-time work of the large farmer households on the agricultural labor productivity. Results indicate that non-agricultural part-time work of large farmer households promotes the agricultural labor productivity, particularly for those with higher non-agricultural incomes, younger age, higher education level and shorter distance between working places in urban sectors and rural residence. At the mean value of the samples, non-agricultural part-time work of the large farmer households will improve agricultural labor productivity by 27.1%. These results remain consistent after we experiment several robustness checks and the instrumental variable method. Further, it is worth stressing that non-agricultural part-time work inhibits the agricultural production for farmer households with labors less than three, while it exhibits positive effects for those with labors more than three. Finally, analysis of mechanism suggests that non-agricultural part-time work of large farmer households enhances the productivity via entering the agricultural association, increasing farm mechanization degree, and promoting the centralized production and farm management on the transferred farmland. It’s suggestive to maintain total area of the transferred farmland to avoid the reverse effects and then the optimal total cultivated area within the range of (100, 200) Mu. Policy implications of our work are discussed.First published online 11 November 2021